Etnopoesia - Bolle, Willi (In:Pandaemonium Germanicum;São Paulo : Humanitas Publicações, 1997-2006;Band 3, Heft 1 (1999), Seite 15-44;22 cm, 1999)
In this Paper, the idea of
urn:nbn:de:hebis:30:3-259939
Keywords: Online-Publikation; Fichte; Hubert; Explosion; Ethnologie; Anthropologie